Analisis Perancangan Harga Pokok Produksi Dengan Metode Activity Based Costing (Study Kasus: Toko Wedday Organizer) - Gurning, Febry Yanti; Lestari, Putri; Purnamasari, Dewi Apriyanti (Jurnal Manajemen Akuntansi (JUMSI), 2024)
Determining an accurate cost of goods sold (COGS) is one of the critical factors in managing a company's finances, especially for small and medium-sized enterprises. One of the methods that can be used to calculate the cost of production more precisely is the Activity Based Costing (ABC) method. This study aims to analyze the application of the ABC method in designing the cost of production at Wedday Organizer Store. The ABC method is used to identify costs associated with production activities and then allocate those costs to products based on the actual use of resources. By conducting this analysis, it is expected that Wedday Organizer Store can obtain more accurate and efficient cost of production calculations, enabling the determination of competitive selling prices and improving profitability. This research uses a descriptive approach with a case study, involving data collection through interviews, observations, and document analysis. The results of the study indicate that by using the ABC method, Wedday Organizer Store can achieve a more realistic cost of production, which aids in pricing decisions and minimizes resource wastage.